"Prompte et sincere" - "Willing and sincere" / "Bereidwillig en opreg" - Victor E. d'Assonville; Dolf Britz (Acta Theologica)
From text: Calvin’s emblem of an outstretched hand holding a heart is reasonably wellknown in South Africa — along with its symbolic meaning: “I offer my heart”. Less familiar, however, is the complete expression, which could be regarded as Calvin’s life motto: “COR MEUM TIBI OFFERO DOMINO PROMPTE ET SINCERE”1 — “Lord, I offer my heart to you, willing and sincere”. This serves as the inspiration for this congress volume.